Use of Local Culinary to Support Marine Tourism on Mampie Beach Polewali Mandar, Indonesia - Wim Johannes Winowatan; Herry Rachmat Widjaja; Eko Harianto; La Ode Nursalam; Siska Mandalia; Isra Djabbar; Masri Ridwan (Universitas Negeri Gorontalo, 2024)
Maritime tourism is synonymous with natural beauty, but its culinary riches are often overlooked, even though local cuisine can be a significant tourist attraction, such as at Mampie Beach, whose potential is hidden and neglected amidst the post-COVID-19 crisis. The research method used is a qualitative approach with data collection techniques using interviews, documentation and observation, then analyzed using qualitative descriptive analysis techniques. The research results show much culinary potential, mainly traditional foods such as Baye/Golla Kambu, Kasippi, Coklat Macoa, and Co'ri. as products that can be marketed or sold in the Mampie Beach marine tourism area. However, the lack of awareness and initiative of the community, tourism managers, and local government means that the culinary potential of these traditional foods cannot support the marine tourism of Mampie Beach, so it cannot impact tourism recovery after the COVID-19 pandemic. Therefore, several strategies need to be implemented involving the community, tourism managers and local government to optimize the existing culinary potential: First, holding regular thematic culinary events, where local traders can promote and sell their traditional dishes; Second, establishing partnerships with local businesses such as restaurants, food stalls and local food producers to introduce and serve regional specialties at tourist attractions, and Third, carry out culinary tours and cooking courses, where tourists can learn about local culinary culture while enjoying authentic dishes served by local people